2004
DOI: 10.1021/ac030381+
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomated High-Throughput Extraction and Cleanup Method for the Measurement of Polybrominated Diphenyl Ethers, Polybrominated Biphenyls, and Polychlorinated Biphenyls in Human Serum

Abstract: A semiautomated extraction and cleanup method has been developed for the measurement of eight polybrominated diphenyl ethers (PBDEs), 2,2',4,4',5,5'-hexabromobiphenyl (BB-153) and 2,2',4,4',5,5'-hexachlorobiphenyl (CB-153). The method employs automated addition of internal standards ((13)C-labeled), addition of formic acid (denaturation agent), and dilution with water prior to automated overnight extraction using a modular solid-phase extraction (SPE) system. Removal of coextracted biogenic materials was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
197
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(198 citation statements)
references
References 19 publications
1
197
0
Order By: Relevance
“…Each of these existing methods fails to address both of the previously identified major limitations in exposure characterization for epidemiologic research on PBB exposure, improvement in LOD and unequivocal determination of multiple congeners. Our method is comparable in performance in terms of LOD for the best existing method (26), and allows for quantification of multiple additional congeners with confidence, given method accuracies for all target compounds that range from 84 to 119% with RSDs <19%. Because individual congeners may contribute differently to toxicity, previous methods are insufficient to characterize human exposure for the evaluation of human health effects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Each of these existing methods fails to address both of the previously identified major limitations in exposure characterization for epidemiologic research on PBB exposure, improvement in LOD and unequivocal determination of multiple congeners. Our method is comparable in performance in terms of LOD for the best existing method (26), and allows for quantification of multiple additional congeners with confidence, given method accuracies for all target compounds that range from 84 to 119% with RSDs <19%. Because individual congeners may contribute differently to toxicity, previous methods are insufficient to characterize human exposure for the evaluation of human health effects.…”
Section: Discussionmentioning
confidence: 97%
“…gas chromatograph-high resolution mass spectrometry (GC-HRMS) is considered the most selective and specific approach used to date although it is more costly, less robust and requires more specialized training as compared to GC-MS-MS. Four studies (26)(27)(28)(29) have utilized GC-HRMS but only one had significant method development and validation information available (6,26). Sjödin et al (6) reported an extraction and cleanup method for measurement of PBBs, PBDEs and PCBs in human serum, and included precision and recovery data as well as congener-specific LODs.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding the analysis of the plasma samples for PBDEs are given elsewhere (Hovander et al 2000;Sjodin et al 2004). Briefly, the samples were automatically fortified with 13 Clabeled internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…The analytical separation was performed on a Rxi-5HT 15 m × 0.25 mm ID × 0.1 µm capillary column (Restek, Bellefonte, PA). Preparation of the samples by solid-phase extraction of the plasma samples was performed with two steps as described by (27). Due to PBDEs lipophilic characteristics, they were normalized to the total lipid content of the plasma sample and were reported as ng/g lipid.…”
Section: Pbde Analysismentioning
confidence: 99%